Desain Manajemen Kurikulum Sekolah Umum - Muhammad Alfiansyah; Nazaruddin Nazaruddin; Yuni Afrilita (At-Tafkir, 2021)
Curriculum management is concerned with how a curriculum is designed, implemented, and controlled (evaluated and ultimately refined) by who carries it out, when it is timed, and within which scope it is implemented. The purpose of this study is to describe the steps to develop curriculum management that is standardized and adjusts to the development of the community so that there can be a mutually beneficial relationship between school and community citizens. The research method used is the research library model. The results of the study showed that curriculum management is structured based on the basic concepts of curriculum management and learning starting from curriculum planning and learning, school work programs, and finally curriculum evaluation and learning.